Kinetics of methyldiethanolamine mineralization by using UV/H2O2 Process - Harimurti, S. (2013)
The UV/H2O2 is one of the popular techniques in the advanced oxidation processes (AOPs) and has been applied in the wastewater treatment during recent two decades. UV exposure on the H2O2 generate highly reactive hydroxyl radicals (OHâ¢), which are used to degrade organic contaminants through oxidation processes in wastewater. This present study involves the estimation of hydroxyl radical rate constants of methyldiethanolamine (MDEA) mineralization at different temperatures by using UV/H2O2 in aqueous solution. Laboratory experiments have been conducted and the profile of MDEA mineralization has been established. The hydroxyl radical rate constants and the activation energy of mineralization process have been calculated. The estimated hydroxyl rate constants and the activation energy are in good agreement with those reported in the literature. Â© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.